Study of Analog Rice from Modified Kimpul Flour, Corn Flour, and Rice Field Snail (Pila ampullacea) Flour on Its Chemical and Sensory Characteristics - Sabilla Choirun Nisak; Rosida, Dedin Finatsiyatull (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Analog rice is an imitation of rice made from ingredients such as tubers and cereals that look like rice. In this study, analog rice will be made from the addition of modified kimpul flour, corn flour, and Rice Field Snail flour. The purpose of this study was to determine the effect of the addition of modified kimpul flour and corn flour with Rice Field Snail flour on the quality of analog rice and to get the best treatment for the addition of modified kimpul flour and corn flour with Rice Field Snail flour on the quality of analog rice that consumers like. This study uses a Completely Randomized Design (CRD) with two factors: the first factor is the mix of modified kimpul flour and corn flour in three different ratios (60%:40%, 70%:30%, and 80%:20%), and the second factor is the amount of Rice Field Snail flour in three different levels (5%, 10%, and 15%).  The data obtained from the analysis were processed using analysis of variance (ANOVA) to determine the presence of significant differences in each treatment. If there is a significant difference, then further tests are carried out with the DMRT (Duncan's Multiple Range Test) method at 5%. The best treatment results were obtained by analog rice with the treatment of adding the proportion of modified kimpul flour and corn flour (70%:30%) with 15% rice field snail flour, which produced a moisture content of 8.24%, an ash content of 4.53%, a fat content of 1.02%, a starch content of 30.37%, a resistant starch content of 10.50%, a protein content of 12.01%, a rehydration capacity of 113.89%, and a volume expansion of 120.79%, as well as texture (3.52), color (3.20), taste (3.40), and aroma (3.68). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action